Diagnostic Model of Superficial Lymph Nodes Based on Clinical History and Ultrasound Findings: A Prospective Cohort Study - Tan, Xiao-Qu; Qian, Lin-Xue; Zhao, Jun-Feng; Sun, Peng-Fei; Li, Qing-Qing; Feng, Ruo-Xuan (Frontiers in Oncology, 2022)
Objectives Differentiation of benign and malignant changes in lymph nodes is extremely important. We aimed to identify the ultrasound and clinical diagnostic criteria permitting this differentiation. Methods Clinical and ultrasound data were collected at Beijing Friendship Hospital from May 2019 to November 2020. Univariate and multivariate analysis were performed using statistical methods, and a mathematical model was established to evaluate benign and malignant lymph nodes. Results A total of 1343 LNs (person) with US‐guided core needle or fine needle biopsy (CNB or FNB) were evaluated in the analysis. Variables with a high predictive power were sex (odds ratio, OR: 3.360, p<0.001), short diameter (OR: 4.660, p<0.001), short/long diameter (S/L) ratio (OR: 1.515, P=0.007), border (OR: 1.626, p=0.002), cortex echogenicity (OR: 2.089, P<0.001), fusion (OR: 2.313, p=0.002), vascularity (peripheral vascularity, OR: 3.424, p<0.001; mixed vascularity, OR: 4.127, p<0.001), and medical history (fever/local pain, OR: 0.316, p<0.001; tumor history in the drainage area, OR: 4.595, p<0.001; both, OR: 5.554, p<0.001). The cut-off score on receiver operating characteristic (ROC) curve analysis using these eight variables was 2.5. The largest area under the ROC curve (Az) value was 82.3% (95% confidence interval (CI), 0.805–0.851), and the sensitivity (79.4%), specificity (72.3%), and accuracy (74.8%) were higher than those for nearly all the single indices. Conclusion The model of combination of ultrasound and clinical symptoms can preliminarily evaluate the benign and malignant of lymph nodes.